2004
DOI: 10.1093/toxsci/kfi069
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and Hemoglobin Adduct Formation of Acrylamide in Humans

Abstract: Acrylamide (AM), used in the manufacture of polyacrylamide and grouting agents, is produced during the cooking of foods. Workplace exposure to AM can occur through the dermal and inhalation routes. The objectives of this study were to evaluate the metabolism of AM in humans following oral administration, to compare hemoglobin adduct formation on oral and dermal administration, and to measure hormone levels. The health of the people exposed under controlled conditions was continually monitored. Prior to conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
153
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(169 citation statements)
references
References 36 publications
8
153
1
7
Order By: Relevance
“…Epoxidation of equal amounts of acrylamide to glycidamide is 2-4 times less in humans when compared to rodents [11][12][13]. Toxicokinetic studies in humans indicated that 60% of absorbed acrylamide is mostly eliminated in urine (86%) as GSH and just 4.4% of this incoming acrylamide was unchanged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epoxidation of equal amounts of acrylamide to glycidamide is 2-4 times less in humans when compared to rodents [11][12][13]. Toxicokinetic studies in humans indicated that 60% of absorbed acrylamide is mostly eliminated in urine (86%) as GSH and just 4.4% of this incoming acrylamide was unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Toxicokinetic studies in humans indicated that 60% of absorbed acrylamide is mostly eliminated in urine (86%) as GSH and just 4.4% of this incoming acrylamide was unchanged. A small amount of unchanged glycidamide was also determined in human urine [11]. Acrylamide and its metabolites accumulate in blood by combining with hemoglobin.…”
Section: Introductionmentioning
confidence: 99%
“…Toxicokinetics of acrylamide were investigated mainly in rodents, whereas recently, some data on acrylamide disposition in healthy volunteers after acrylamide administration in a test-meal (8,9), in drinking water (10,11), or dermally (12) have been published. As shown in rats and mice (6,10,13) and in humans (8)(9)(10), acrylamide is readily absorbed and widely distributed to tissues, crosses the human placenta, and is transferred into the breast milk (8,14).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in rats and mice (6,10,13) and in humans (8)(9)(10), acrylamide is readily absorbed and widely distributed to tissues, crosses the human placenta, and is transferred into the breast milk (8,14). Acrylamide is in part biotransformed to the epoxide glycidamide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation